Physicochemical Characterization of Native and Steam Explosion Pretreated Wild Sugarcane (Saccharum spontaneum) - Aruna Selvaraj; Gobikrishnan Sriramulu (Center of Biomass & Renewable Energy, Diponegoro University, 2020)
The technology of biomass conversion to bioethanol primarily based on pretreatment, enzymatic hydrolysis, and fermentation. This study was to investigate the effectiveness of the steam explosion pretreatment of Saccharum spontaneum L., which accomplishes the greater efficacy of physicochemical and structural properties. The collected plant material was processed and analyzed for ash, moisture, Carbon content, and other elements. The cellulose content of pretreated biomass was increased to 54.31% when compared to native wild sugarcane 41.23% due to the removal of lignin. SEM and FTIR results identified the changes in structural and functional groups also the BET analysis confirmed the increased surface area of Pretreated biomass is 55.541m²/g whereas the surface area of native biomass is 17.939 m²/g, this is due to the increase in pore volume and pore diameter of pretreated wild sugarcane which is 0.260 cc/g and 9.712 nm when compared to pore volume and Pore Diameter Dv(d) of raw material is 0.040 cc/g and 3.650 nm. XRD crystallinity pattern of pretreated wild sugarcane showed an increase in the crystallinity index due to the breakage of lignin during pretreatment. This comparative study has been carried out to know the effect of steam explosion pretreatment over the physicochemical composition and structural changes of wild sugarcane for sustainable bioethanol production.